Variability in Treatment for Carbon Monoxide Poisoning in Japan: A Multicenter Retrospective Survey - Motoki Fujita; Yasutaka Oda; Kotaro Kaneda; Yoshikatsu Kawamura; Takashi Nakahara; Masaki Todani; Takeshi Yagi; Yasutaka Koga; Ryosuke Tsuruta (Emergency Medicine International)
Background. The aim of this study was to identify practice differences in the treatment of carbon monoxide (CO) poisoning with or without hyperbaric oxygen (HBO2) therapy in Japan. Materials and Methods. Using an online survey website (Google form), we created a questionnaire and invited interested institutions to join the COP-J Study, a prospective observational study of CO poisoning in Japan. Results. Forty-eight (63%) of 76 institutions replied to the questionnaire. Thirty-three institutions (69%) administered HBO2 therapy to patients with CO poisoning, and 15 institutions (31%) did not. Consciousness disturbance on arrival, exposure to CO for a long time, and elevation of arterial carboxyhemoglobin (CO-Hb) were the major indications for HBO2 therapy. The maximum therapeutic pressures were 2.0, 2.5, and 2.8 atmospheres absolute (ATA) at 19 (58%), 6 (18%), and 8 (24%) institutions, respectively. The number of HBO2 sessions on the first day was 1–3, and 1–7 sessions were administered on days 2–7. Seventeen (35%) institutions treated patients with delayed neurological sequelae (DNS) and 15 of them used HBO2 therapy for DNS. Conclusions. This survey indicates that HBO2 therapy for CO poisoning was varied in both the indications and practice regimens used in Japan.